Kompetensi Manajerial Kepala Sekolah dalam Meningkatkan Kinerja Personil Sekolah pada SMP Negeri 1 Banda Aceh - Aisyah, Murniati, Niswanto. (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
Managerial competency of principality is one of factors determined performance school personnel and the success of education in school. The research aimed to gained overviews on managerial competency of principality in program arrangement. The program implementation to improved school personnel performance. . The constraints faced by principal implementing the programme of increasing the school staffs’ performance. This research used descriptive method with qualitative approach. Technique of data collection were observation, interview, and documentation. The subject of this research were head master, vice principal, teacher, head of administrative, laboran, and librarian. The result of this research showed that: (1) Managerial competency of principal in this study has superiority in the process of planning the programme namely: The competency applied the vision, mission, and goals of the school. The programme of increasing the school staffs’ performance was running well. It could be seen from the structure of school organisation in arranging planning work and administration of the school. (2) Managerial competency of principal in increasing the school staffs’ performance did not targeted standard since the management of educational mediums, budgeting, and its organisation were not optimally optimised. (3) There were also constrains faced by the stakeholders in implementing the programme of increasing the school staffs’ performance. One of them was the organised plan, which became unorganised one during the implementation. Low budgeting also contributed to the constraints. Moreover, as mentioned above, the discontinuous trainings and unfollow-up supervision also forced the implementation of the program.